The Influence of INSTAD Learning Strategies Toward Metacognition And Student’s Cognitive Achievement In Studying Biology - Kistantia Elok Mumpuni; Puguh Karyanto; Bowo Sugiyarto (Universitas Sebelas Maret, 2012)
Learning biodiversity using INSTAD learning strategy to improve metacognition awareness and student’s cognitive achievement : a study toward student of SMA Batik 1 Surakarta.This research is considered as a quantitative research, and analyzed as according to quasi-experimental paradigm. The research was designed using pretest-posttest randomized subject control-group. Experimental group was determined and upon which INSTAD strategy was applied. Instead of the non experiment one. Such the aforementioned strategy was conducted upon student of SMA Batik 1 Surakarta as a population. Sampling was taken randomly upon two chosen the X-5 (experiment class) and the X-4 (control class). Data was collected using questionnaire, test and observation form. The data were analyzed by anacova.Results of the study showed that metacognition was significantly affected by INSTAD. However the application of INSTAD has taken effect on student’s cognitive achievement in studying biology of SMA Batik 1 Surakarta. Key Words: INSTAD learning strategies, metacognition, student’s cognitive achievement